SERVICE-LEARNING DALAM PENDIDIKAN ARSITEKTUR: MOMEN KRITIS DALAM SUATU REFLEKSI - Sylviana Putri Sunario Soegondo; Lilianny S. Arifin (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2020)
Title: Service-Learning in Architecture Education: A Critical Moment in A Reflection For over the years, service-learning pedagogy is understood as an appropriate method in experiential education because it focuses on initiatives that has the capacity to change the social well–being of individuals and students' commitment to society's general well–being. Learning entails transformation both individually and from the social work experience through reflection. Geleta and Gilliam (2003) said that reflection is a critical element that connect the service experience in meaningful ways with students' thoughts, sensations, and values. There are four key elements to support practical strategies for meaningful reflection: continuity and connectivity in reflective process on the learning experience and objectives, higher-level thinking, atmosphere of trust and mutual respect, and contextual reflection. This paper explores the implications of contextual reflection about critical moment when an individual experience is shared and become tacit knowledge. The journal reflection from architecture students 5th semester was categorized using content analysis methods to find a personal experience before and after doing a project that can be grasped as tacit knowledge to become explicit knowledge that enhances character development as an architecture student.